How do exporters react to changes in cost competitiveness? - Stefaan Decramer; Catherine Fuss; Jozef Konings (National Bank of Belgium, 2015)
Policy-making institutions such as the European Commission, the ECB and the OECD often use unit labor costs as a measure of international competitiveness. The goal of this paper is to examine how well this measure is related to international export performance at the firm level. To this end, we use Belgian firm-level data for the period 1999-2010 to analyze the impact of unit labor costs on exports. We use exports adjusted for their import content. We find a statistically significant negative effect of unit labor costs on export performance of firms with an estimated elasticity of the intensive margin of exports ranging between -0.2 and -0.4. This result is robust to various specifications, including firm, time and sector fixed effects and estimation approaches. We find that this elasticity varies between sectors and between firms, with firms that are more labor-intensive having a higher elasticity of exports with respect to unit labor costs. The micro data also enable us to analyze the impact of unit labor costs on the extensive margin. Our results show that higher unit labor costs reduce the probability of starting to export for non-exporters and increase the probability of exporters stopping. While our results show that unit labor costs have an impact on the intensive margin and extensive margin of firm-level exports, the effect is rather low, suggesting that passthrough of costs into prices is limited or that demand for exported products is not elastic. The latter is consistent with recent trade models emphasizing that not only relative costs, but also demand factors such as quality and taste matter for explaining firm-level exports.
Keywords: F1; F4; F16; 330; unit labor costs; exports; competitiveness; heterogeneity; Lohnstückkosten; Internationaler Wettbewerb; Export; Schätzung; Belgien